One-Flask Synthesis of Dinucleoside Tetra- and Pentaphosphates - Han, Qianwei (2006)
[Image: see text] We report a one-flask route for synthesis of dinucleoside tetra and pentaphosphates, in isolated yields of 50 to 85%. This route relies on a mixture of PIII and PV chemistries, using phosphitylation of a protected nucleoside with 2-chloro-4H-l,3,2-benzo-dioxaphosphorin-4-one (salicylchlorophosphite), followed by sequential reaction with inorganic pyrophosphate, and a nucleoside 5′ mono- or diphosphate.